The Spiderwick Chronciles: The Ironwood Tree - DiTerlizzi, Tony.; Fairies - Fiction (New York Simon & Schuster Books for Young Readers, 2004)
Can three weary children face an ogre with an evil plan to conquer the planet and poison the land?
5 - 9
Keywords: Ogres - Fiction; Brothers and sisters - Fiction